A review of the genus Boccardia Carazzi (Polychaeta Spionidae) with description of two new species - Blake, James A.; Woodwick, Keith H. (Bulletin of the Southern California Academy of Sciences, 1971)
Taxonomic characteristics of 14 species of Boccardia are compiled in the form of a table. Each species is further distinguished in a key. Boccardia ligerica Ferronnière is redescribed with new synonymies. Two new species, B. berkeleyorum and B. chilensis are described.
World Polychaeta Database (WPolyDb) Publication date: 27 August 1971